if p(x) = 2x cube – x square + 3x +1 , find the value of p(-1) + p(1) – p(2)​

if p(x) = 2x cube – x square + 3x +1 , find the value of p(-1) + p(1) – p(2)​

2 thoughts on “if p(x) = 2x cube – x square + 3x +1 , find the value of p(-1) + p(1) – p(2)​”

  1. 2x^3-x^2+3x+1
    p(x)
    i)p(-1)=2(-1)^3-(-1)^2+3(-1)+1
    =2*-1-1+(-3)+1
    =-2-1-3+1
    =-5
    ii)p(1)=2(1)^3-(1)^2+3*1+1
    =2*1-1+3+1
    =2-1+3+1
    =5
    iii)p(2)=2(2)^3-(2)^2+3*2+1
    =2*8-4+6+1
    =16-4+6+1
    =19
    So, p(-1)+p(1)-p(2)
    =-5+5-19
    =-19 Ans.
    Mark as brainliest

  2. p(x)=2x³-x²+3x+1

    p(-1)=2(-1)³-(-1)²+3(-1)+1

    =-2-1-3+1

    = -5

    p(1)=2(1)³-(1)²+3(1)+1

    =2-1+3+1

    =5

    p(2)=2(2)³-(2)²+3(2)+1

    =16-4+6+1

    =19

    p(-1)+p(1)-p(2)

    -5+5+19

    =19

Leave a Comment